The Modernization of Madrasah in the Millenial Era of KH Abdul Wahid Hasyim Perspective - Muvid, Muhamad Basyrul (Tribakti: Jurnal Pemikiran Keislaman, 2021)
Madrasah as a form of identity from Islamic education serves as an educational institution that not only organizes religious-based learning but also provides the general subject matter. The purpose of this research is to try to find the ideas and buzz of KH. A Wahid Hasyim in modernizing madrassas so that they can always exist in the midst of the dynamics of the times. The research method used is the study of literature which is to collect various literature relevant to the topic being studied. The results of this study show that KH. A Wahid Hasyim has a mission vision to perform various learning methods, integrate the general religious curriculum, activate the library: improve the hobby of reading, spread the motivation of learning and encourage work, gender equality in religious education, and build the ideal management of Islamic education.